1994
DOI: 10.1148/radiology.192.2.8029429
|View full text |Cite
|
Sign up to set email alerts
|

Distal ureteral calculi: detection with vaginal US.

Abstract: In symptomatic female patients, use of vaginal sonography should be considered to evaluate the distal ureter for calculi, particularly if the results of transabdominal examination are normal or inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(57 citation statements)
references
References 0 publications
1
52
0
4
Order By: Relevance
“…Laing et al reported detection of 13 distal ureteral stones, where transabdominal scan had detected only two of the 13 stones. 41 Sensitivity for stone detection may also be improved in pregnancy by using Doppler US to measure renal vascular resistance. Measurement of the resistive index (RI) of intrarenal blood flow has shown that using a threshold of 0.70 for RI and a change in RI of 0.06 is useful in the diagnosis of acute unilateral ureteral obstruction, if done within 6-48 h of presentation (sensitivity 45%, specificity 91% and sensitivity 95%, specificity 100%, respectively).…”
Section: Ultrasonographymentioning
confidence: 99%
“…Laing et al reported detection of 13 distal ureteral stones, where transabdominal scan had detected only two of the 13 stones. 41 Sensitivity for stone detection may also be improved in pregnancy by using Doppler US to measure renal vascular resistance. Measurement of the resistive index (RI) of intrarenal blood flow has shown that using a threshold of 0.70 for RI and a change in RI of 0.06 is useful in the diagnosis of acute unilateral ureteral obstruction, if done within 6-48 h of presentation (sensitivity 45%, specificity 91% and sensitivity 95%, specificity 100%, respectively).…”
Section: Ultrasonographymentioning
confidence: 99%
“…Nestes casos deve-se utilizar a US e a RM como métodos de rastreamento e detalhamento anatômico. A US é bastante sensível para a detecção de cálculos nas vias urinárias, perdendo em eficácia quando o cálculo encontra-se localizado no ureter distal; nestes casos a US endovaginal pode ser alternativa diagnós-tica eficiente (31) . Quando a urografia excretora é indispensável pode-se reduzir a dose de radiação realizando-se apenas uma radiografia dez minutos após a injeção endovenosa do contraste; desta forma, é possí-vel identificar os sistemas coletores e eventuais obstruções.…”
Section: Exames Radiológicos Durante a Gestaçãounclassified
“…The second limitation is the impossibility of evaluating the ureter below the level of the pelvic brim/iliac artery in most cases as well as situations in which the 289 Archivio Italiano di Urologia e Andrologia 2017; 89, 4 Ureteroscopy in pregnant women and premature labor investigator is unable to differentiate between secondary ureteral obstruction from calculi and the physiologic hydronephrosis of pregnancy (14). Transvaginal USG is another diagnostic tool that can be used to accurately detect distal ureteral stones as demonstrated in the literature and can be performed to evaluate the length of the uterine cervix in a one-step procedure (15). In pregnant patients, ionizing radiation may have teratogenic effects on the fetus and should be avoided, diminishing clinicians' diagnostic options in complicated cases.…”
Section: Discussionmentioning
confidence: 99%